The Effects of Multi-Day vs. Single Pre-exercise Nitrate Supplement Dosing on Simulated Cycling Time Trial Performance and Skeletal Muscle Oxygenation. Issue 1 (January 2019) - Jo, Edward; Fischer, Michelle; Auslander, Alexandra T.; Beigarten, Alan; Daggy, Bruce; Hansen, Ken; Kessler, Lisa; Osmond, Adam; Wang, Hong; Wes, Rachel
Abstract : Abstract: Jo, E, Fischer, M, Auslander, AT, Beigarten, A, Daggy, B, Hansen, K, Kessler, L, Osmond, A, Wang, H, and Wes, R. The effects of multiday vs. single pre-exercise nitrate supplement dosing on simulated cycling time trial performance and skeletal muscle oxygenation. J Strength Cond Res 33(1): 217–224, 2019—A transient augmentation in the metabolic efficiency of skeletal muscle is the purported basis for dietary nitrate supplementation amongst competitive and recreational athletes alike. Previous studies support the ergogenic effects of nitrate supplementation, as findings indicated improved microvascular blood flow, exercise economy, and performance with relatively short-term supplementation. As with most ergogenic aids, the optimum duration of supplementation before performance or competition, i.e., loading phase, is a critical determinant for efficacy. Therefore, the purpose of this study was to investigate the effects of long-term vs. single dosing nitrate supplementation on skeletal muscle oxygenation and cycling performance. In a randomized, placebo controlled, double blind, parallel design study, healthy, recreationally active men ( n = 15) and women ( n = 14) subjects (age = 18–29 years) completed an 8 km (5 mi) simulated cycling time trial before and after a 14-day supplementation period with either a nitrate supplement (Multi-Day Dosing Group) ( n = 14) or placebo (Single Pre-Exercise Dosing Group; SD) ( n = 15). Both groups consumed a single dose of the nitrate supplement 2 hours before the post-treatment time trial. In addition, skeletal muscle oxygenation was measured via near-infrared spectroscopy during each time trial. Multiday nitrate supplementation significantly decreased time to completion ( p = 0.01) and increased average power ( p = 0.04) and speed ( p = 0.02) from pre-to post-treatment, while a single dosing produced no significant changes to these measures. There were no significant differences over time and across treatments for any other measures including muscle oxygenation variables. Overall, long-term nitrate supplementation appears to have an advantage over a single pre-exercise dosing on cycling performance and metabolic efficiency as indicated by an increase in power output with no change in oxygenation.